Jakarta punya cara - Alkatiri, Zeffry J., 1960- (Depok : Masup Jakarta, 2012)
History of Jakarta and its social life and customs.
Continues: Pasar Gambir, komik Cina & es Shanghai.
Includes bibliographical references (p. 133-134) and index.
Keywords: Jakarta (Indonesia) -- Social life and customs; Jakarta (Indonesia) -- History